Skeletal Lead Burden of the British Royal Navy in Colonial Antigua. (3rd May 2017) - Giffin, K. L.; Swanston, T.; Coulthard, I.; Murphy, A. R.; Cooper, D. M. L.; Varney, T. L.
Abstract: Lead (Pb) has been known to be a cause of human poisoning since ancient times, but despite this, it was a widely used metal in the European colonial period. In this study, the relationship between Pb exposure and the demographic variables ancestry and age was explored by comparing the bone Pb levels of individuals that were of either African or European ancestry, excavated from a British Royal Navy hospital cemetery (1793–1822 CE) at English Harbour in Antigua, West Indies. More direct comparisons of Pb levels between the two ancestral groups were possible in this study because of the unsegregated nature of this cemetery. Inductively coupled plasma mass spectrometry was used to determine bulk Pb levels in cortical bone samples from the fibular diaphyses of 23 male individuals. No significant difference was found between the distributions of the Pb levels of the ancestral groups ( p  = 0.94). Further, no positive correlations or significant differences were found in relation to the individuals' ages and their Pb levels ( p  = 0.24). Levels of Ba, Ca and rare earth elements support a largely biogenic origin of lead. This is bolstered by Pb deposition patterns, generated by synchrotron X‐ray fluorescence imaging for another study. The data suggest that naval personnel, regardless of ancestry at English Harbour, had very similar experiences with regard to Pb exposure. Their exposure to the toxic metal was likely not consistent over time as steady exposure would have resulted in accumulation of Pb with age. This study contributes to addressing historical questions regarding the prevalence of Pb poisoning within the British Royal Navy during the colonial period. © 2017 The Authors International Journal of Osteoarchaeology Published by John Wiley & Sons Ltd.